Detection of New Delhi metallo-beta-lactamase enzyme gene blaNDM-1 associated with the Int-1 gene in Gram-negative bacteria collected from the effluent treatment plant of a tuberculosis care hospital in Delhi, India. Issue 6 (1st June 2020) - Aggarwal, Amit; Bhalla, Manpreet; Fatima, Khan Hena
Abstract : Background. Organisms possessing the bla NDM-1 gene (responsible for carbapenem resistance) with a class-1 integron can acquire many other antibiotic resistance genes from the community sewage pool and become multidrug-resistant superbugs. In this regard, hospital sewage, which contains a large quantity of residual antibiotics, metals and disinfectants, is being recognized as a significant cause of antimicrobial resistance (AMR) origination and spread across the major centres of the world and is thus routinely investigated as a marker for tracing the origin of drug resistance. Therefore, in this study, an attempt has been made to identify and characterize the carbapenem-resistant microbes associated with integron genes amongst the organisms isolated from the effluent treatment plant (ETP) installed in a tertiary respiratory care hospital in Delhi, India. Methods. One hundred and thirty-eight organisms belonging to Escherichia, Klebsiella, Pseudomonas and Acinetobacter spp. were collected from the incoming and outgoing sewage lines of the ETP. Carbapenem sensitivity and characterization was performed by the imipenem and imipenem-EDTA disc diffusion method. Later DNA extraction and PCR steps were performed for the Int-1 and bla NDM-1 genes. Results. Of the 138 organisms, 86 (62.3 %) were imipenem-resistant ( P <0.05). One hundred and twenty-four (89.9 %) organisms had one or both of the genes. Overall, the bla NDM-1 gene (genotypic resistance) was present in 71 % (98/138) of organisms. 53.6 % (74/138) organisms were double gene-positive ( bla NDM-1 + Int-1), of which 40 were producing the metallo-beta-lactamase enzyme, making up almost 28.9 % (40/138) of the collected organisms. Conclusion. The current study strengthens the hypothesis that Carbapenem resistant organisms are in a high-circulation burden through the human gut and hospital ETPs are providing an environment for resistance origination and amplification.